Analisis Faktor Penyebab Banjir Di Kecamatan Jombang Dengan Model Sistem Dinamik - Sinaga, Mikhael Fernand; Setiadji, Bayu Rizqi; Hidayat, Rahmat; Sahrupi, Sahrupi (Fakultas Teknik Universitas Tulang Bawang, 2024)
Cilegon City is an area that has a high level of vulnerability to various disasters, including natural disasters. Natural disasters are events that are natural and have the potential to cause damage and destruction to the environment, with impacts in the form of loss of life, material loss, and damage to infrastructure that has been developed over some time. Based on the Cilegon City Regional Disaster Management Agency (BPBD), flooding is a frequent natural disaster in Cilegon City. This research aims to identify the factors that cause flooding in the Jombang Subdistrict area. The research stages are observation, data collection, data processing with the causal loop diagram approach, data validation, data analysis, and conclusion. The results of the analysis show that the main factors causing flooding in Jombang Subdistrict are the intensity of rainfall, small drainage, and the small number of absorption wells. The consequences caused by floods are property damage, the spread of disease, economic losses, environmental damage, infrastructure disruption, and social disruption. Therefore, the solution to flooding in Jombang Subdistrict is to expand drainage, add the number of absorption wells, provide education to the community about environmentally friendly behavior, and green the environment. Keywords: Cilegon, Causal Loop Diagram, Dynamic System, Flooding